Mode of Injury, Involvement of Bones and Post-Operative Surgical Outcomes of Patients presented with Lower Limbs Fractures attended at a Tertiary Care Hospital at Tourist City of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Surgical management is very much crucial among the lower limb fracture patients.Objective: The purpose of the present study was to find out the mode of injury, involvement of bones and post-operative surgical outcomes of patients presented with lower limbs fractures patients.Methodology: This prospective hospital-based study was conducted in the Department of Orthopaedic and Traumatology at Cox’s Bazar Medical College Hospital, Cox’s bazar, Bangladesh from January 2019 to June 2022 for a period of three and half years. All the patients who were presented with the clinical features of fracture of lower limbs were selected as study population. The patients were managed by conservative or surgical way. The outcomes of both procedures were recorded.Results: A total number of 370 cases were recruited for this study. The mean age with SD of the study population was 18.2±11.56 years. Among these road traffic accident was the most common mode of injury which was 204(55.0%) cases. Open type of fracture was found in 141(38.0%) cases and the close was found in 229(62.0%) cases. The most common bones involved was the shaft of tibia and fibula which was 159(43.0%) cases. During conservative treatment mal-union was reported in 193(66.8%) cases and the rest of the 96(33.2%) patients had shown the stiffness. Among 81 operated cases majority were recovered which was 70(86.0%) cases. However, death was found in 2(2.0%) cases. Minor and major infection were reported in 6(8.0%) cases and 3(4.0%) cases respectively.Conclusion: In conclusion the most common mode of injury is road traffic accident with the involvement of shaft of tibia and fibula with majority improvement.[Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):60-64]